2014
DOI: 10.1093/oep/gpu032
|View full text |Cite
|
Sign up to set email alerts
|

Climate shocks, dynastic cycles and nomadic conquests: evidence from historical China

Abstract: Nomadic conquests have helped shape world history, yet we know little about why they occurred. Using a unique climate and dynastic data set from historical China dating from 221 BCE, this study finds that the likelihood of nomadic conquest increases with less rainfall proxied by drought disasters, which drove pastoral nomads to attack agrarian Chinese for survival. Moreover, consistent with the dynastic cycle hypothesis, the likelihood of China being conquered increases with the number of years earlier that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…From the perspective of history, Wang et al [6] and Zhang [7] confirm that floods in ancient China often damaged the agriculture in the Huaihe River district. Chen [8,9] argues that climate shocks played an important role in nomadic conquest and peasant uprisings, indirectly impeding economic development.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of history, Wang et al [6] and Zhang [7] confirm that floods in ancient China often damaged the agriculture in the Huaihe River district. Chen [8,9] argues that climate shocks played an important role in nomadic conquest and peasant uprisings, indirectly impeding economic development.…”
Section: Introductionmentioning
confidence: 99%
“…Greater demand for urban jobs can exert downward pressure on wages and trigger migration to more distant places or other countries, possibly with far-reaching effects (Maurel and Tuccio 2016). Beyond the impact on economic growth, climate-induced shocks have been linked to higher incidence of civil conflict in Brazil (Naidoo et al 2009) and Somalia (Maystadt and Ecker 2014), and over long historical periods in the Arab Republic of Egypt (Chaney 2013) and China (Chen 2015;Kung and Bai 2011) where it has also been shown that agronomic advances can help to mitigate these effects (Jia 2014).…”
Section: The Far-reaching Impacts Of Climate Changementioning
confidence: 99%
“…to 1994 using stalagmite layer thickness from Shihua Cave near Beijing. Chen (2014Chen ( , 2015 uses this same source when examining how climate affected peasant uprisings and nomadic incursions into China. Büntgen et al (2011) use tree rings form various locations to measure temperature anomalies during the summer months in Central Europe from 500 BCE to present day, also at an annual frequency.…”
Section: Explanationsmentioning
confidence: 99%